Dietary behaviors in newly diagnosed youth with inflammatory bowel disease. Issue 4 (2nd October 2017) - Hagin, Sarah; Lobato, Debra J.; Sands, Bruce E.; Korzenik, Joshua R.; Merrick, Marjorie; Shah, Samir A.; Bancroft, Barbara; Bright, Renee; Law, Meaghan; Moniz, Heather; Shapiro, Jason; LeLeiko, Neal S.
ABSTRACT: The impact of dietary behaviors on health outcomes in youth with inflammatory bowel disease (IBD) is unclear. The present study examined dietary behaviors and their association with biomedical factors in youth with IBD. Eighty-six newly diagnosed youth (mean age = 12.6) were included in analyses. Biomedical factors included disease activity and inflammatory markers. Despite adequate total caloric intake, estimated nutrient and fruit and vegetable intakes were below recommended levels. There was a significant negative association between vegetable intake and C-Reactive Protein ( p = 0.04). Results suggest that dietary behaviors play an important role in IBD health outcomes.